Guest Acceptors with Lower Electrostatic Potential in Ternary Organic Solar Cells for Minimizing Voltage Losses - Yang, Shuncheng (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.